Effect of quenching medium, solution treatment, and aging parameters on mechanical properties of Aluminum alloy 6061 - Pshtiwan Karim; Rekawt Amin; Hawre Amin; Abbas Khwakaram; Omer Mahmood (Engineering and Technology Journal)
This study demonstrates the effect of quenching medium, solution treatment, and aging parameters on the mechanical properties of Aluminum alloy 6061. To select an optimal quenching medium from three distinct quenching media (corn, sunflower, and sesame oil), solution heat treatment was conducted on three impact test samples at 545 ℃ for 2 hours, and then quenching was conducted in the mentioned quenching medium. Consequently, sesame oil demonstrated the lowest shock absorption rate; thus, sesame oil was selected as the quenching medium. As a result, every sample for tensile, hardness, and impact tests underwent solution heat treatment at 545 ℃ for 2 hours, followed by quenching in sesame oil to room temperature, and subsequent artificial aging at temperatures of 180 ℃, 195 ℃, and 210 ℃ for 1, 2, 4 hours. Considerable enhancements in the mechanical properties were observed in tensile strength value and hardness while the ductility decreased. It was observed that the best result was achieved by aging at 195 ℃ for 4 hours, increasing the ultimate tensile strength to 351.413 N/mm2 from the initial value of 260 N/mm2 for the as-received specimen; this is attributed to the formation of finely dispersed grains. In contrast, the ultimate tensile strength for the annealing condition decreased to 152.020 N/mm2 due to forming a coarser grain size. Furthermore, the highest hardness value achieved is 39.10 HRB, achieved by aging at 195 ℃ for 4 hours, compared to the hardness value achieved by annealing conditions at 18.23 HRB.